Bahasa Inggris - Rizqullah, Ayun Anindita (Asosiasi Ahli Administrasi Indonesia, 2023)
The purpose of this study is to investigate the effect of Instagram feeds on the buying interest of students in the city of Bandung. This study uses a quantitative description method. Data collection was carried out by distributing questionnaires to students in the city of Bandung with a total of 110 respondents. The analytical method used is simple linear regression analysis with the aim of knowing the effect of the x variable (Instagram Feed) on the y variable (bandung city students). The results of this analysis are that the appearance of the Instagram feed has an influence of 66.6% on the buying interest of students in the city of Bandung